(Re) evaluating improvisation in commedia dell'Arte. Issue 2 (3rd July 2022) - Crick, Olly
Abstract: The performance history of commedia dell'arte is full of tantalising clues about the genre's relationship with the practice of live improvisation, research into which is often frustrated by ontological and epistemological differences between the 'what happened' approach of historians and the 'how to' approach of performers. The ephemerality of historical performance, compounded by the doubly ephemeral practice of improvisation, puts commedia dell'arte in a place where methodology and mythology struggle for supremacy, and what is performed as commedia today has become a contested area. Within this chapter I will explore three themes that I hope will shed add to this debate and my overall purpose is to demystify a proposed historical improvisational method and make it more accessible.